Fish allergy causing angioedema and secondary angle-closure glaucoma. (6th March 2013) - Calder, Donovan; Calder, Jennifer
Abstract : A 56-year-old woman with a history of primary angle-closure glaucoma presented with acute generalised swelling, and facial angioedema following a fish meal. She complained of nausea, vomiting, headache, pain in both eyes and acute loss of vision. Her visual acuity was reduced and intraocular pressures (IOP) were elevated. Gonioscopy revealed complete angle closure in the left eye and complete to partial closure in the right eye. Through existing peripheral iridotomies the anterior capsules were seen pressed up against the iris of both eyes. A diagnosis of angle-closure glaucoma was made, medications were started to reduce the elevated intraocular pressure and systemic antihistamine to counter the allergic reaction. She was hospitalised for further management. A follow-up at 2 years revealed her visual acuities and IOP had remained normal.